Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

f(x) = x+3
g(x)=2x² - 4
Find (f g)(x)..
OA. (f.g)(x) = 2x³ - 12
B. (f g)(x) = 2x³ + 12
c. (f.g)(x) = 2x³ + 6x² - 4x-12
OD. (f.g)(x) = 2x³ + 6x² + 4x+12


Sagot :

Answer:

I got 2x^3+3x^2-4x-12

Step-by-step explanation:

I hope this helps a little bit